Disabilitas sebagai Dakwah Sunyi: Narasi Resiliensi dan Dinamika Psikososial Mahasiswa dengan Kebutuhan Khusus di Indonesia - Izza Himawanti (IQTIDA : Journal of Da'wah and Communication, 2025)
This study aims to explore the psychosocial dynamics and adjustment processes of students with disabilities in Islamic higher education institutions, focusing on narratives of resilience and the spiritual meaning embodied in the concept of silent da’wah. Using a phenomenological approach and Interpretative Phenomenological Analysis (IPA), data were collected through in-depth interviews with four students with physical and mental disabilities in Pekalongan. The findings reveal that students with disabilities face significant structural, social, and emotional challenges, yet they demonstrate strong resilience through Islamic values such as ṣabr (patience), ikhlāṣ (sincerity), and istiqāmah (steadfastness). Their adjustment journey follows stages from anxiety, self-acknowledgment, and social participation to meaningful contributions through altruism and adaptive conformity. These findings align with prior literature on the role of spiritual guidance in reconstructing happiness and the importance of faith in fostering subjective well-being. The study recommends enhancing inclusive campus support systems and integrating psychospritual approaches into disability services in higher education settings.